Proteome analysis of Ehrlichia chaffeensis containing phagosome membranes revealed the presence of numerous bacterial and host proteins - Kondethimmanahalli, Chandramouli; Ganta, Roman R. (Frontiers in Cellular and Infection Microbiology, 2022)
Tick-transmitted Ehrlichia chaffeensis, the causative agent for human monocytic ehrlichiosis, resides and multiplies within a host cell phagosome. Infection progression of E. chaffeensis includes internalization into a host cell by host cell membrane fusion events following engulfment leading to the formation of E. chaffeensis containing vacuole (ECV). Revealing the molecular composition of ECV is important in understanding the host cellular processes, evasion of host defense pathways and in defining host-pathogen interactions. ECVs purified from infected host cells were analyzed to define both host and bacterial proteomes associated with the phagosome membranes. About 160 bacterial proteins and 2,683 host proteins were identified in the ECV membranes. The host proteins included predominantly known phagosome proteins involved in phagocytic trafficking, fusion of vesicles, protein transport, Ras signaling pathway and pathogenic infection. Many highly expressed proteins were similar to the previously documented proteins of phagosome vacuole membranes containing other obligate pathogenic bacteria. The finding of many bacterial membrane proteins is novel; they included multiple outer membrane proteins, such as the p28-Omps, the 120 kDa protein, preprotein translocases, lipoproteins, metal binding proteins, and chaperonins, although the presence of ankyrin repeat proteins, several Type I and IV secretion system proteins is anticipated. This study demonstrates that ECV membrane is extensively modified by the pathogen. This study represents the first and the most comprehensive description of ECV membrane proteome. The identity of many host and Ehrlichia proteins in the ECV membrane will be a valuable to define pathogenic mechanisms critical for the replication of the pathogen within macrophages.